2014
DOI: 10.4103/0300-1652.129661
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary hypertension in sickle cell anaemia patients of a tertiary hospital in Nigeria

Abstract: Background:Sickle cell disease (SCD) is an inherited haemoglobinopathy characterised by recurrent organ hypoxia-reperfusion cycles which may result in repeated organ damage including the lungs and heart. In SCD, pulmonary hypertension is a known complication that may precede or complicate acute chest syndrome which is often fatal. This study seeks to know the prevalence of pulmonary hypertension and its relationship with clinical and laboratory parameters in sickle cell disease patients attending a tertiary ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
3
12
1
1
Order By: Relevance
“…[ 19 , 20 ] Two Nigerian studies which included children and adults found a wide prevalence of 3.6% to 25%. [ 17 , 18 ] The Western Nigeria study [ 18 ] with prevalence of 3.6% had a small sample size which was about one-third that of the current study and this may have accounted for the low prevalence of PHT found in their cohort. These investigators also proposed that their cohort was highly selective and better motivated for regular care compared to the Northern Nigerian participants.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…[ 19 , 20 ] Two Nigerian studies which included children and adults found a wide prevalence of 3.6% to 25%. [ 17 , 18 ] The Western Nigeria study [ 18 ] with prevalence of 3.6% had a small sample size which was about one-third that of the current study and this may have accounted for the low prevalence of PHT found in their cohort. These investigators also proposed that their cohort was highly selective and better motivated for regular care compared to the Northern Nigerian participants.…”
Section: Discussionmentioning
confidence: 76%
“…In a Western Nigeria study, the authors did not report PHT in any of their controls and there was also a significant difference between the mean peak TRV of the controls and that of SCD patients. [ 18 ] This significant difference in TRV values between SCD patients and controls as well as the very low prevalence of PHT among control subjects suggests a contributory effect of the haemoglobin genotype on the degree of tricuspid regurgitation velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary arterial hypertension is defined by end systolic pressure in the right ventricle greater than 25 mmHg (normal is less than 15 mmHg). In a cohort of Nigerian SCD patients, 2 (3.6%) out of 56 met the criteria for pulmonary hypertension [ 125 ]. Tricuspid regurgitation jet velocity of >2.5 m/sec is associated with a high risk of pulmonary hypertension and is an independent risk factor for death [ 128 ].…”
Section: Clinical Phenotypes and Complications In Sickle Cell Disementioning
confidence: 99%
“…The prevalence of 23.9% seen in this study is comparable to the findings of another study in Zaria (Northern Nigeria) by Aliyu et al20 who made use of peak TRV of ≥2.5 m/s as a criterion and found a prevalence of 25%. Dosunmu et al21 in a study in Lagos, Nigeria, got a much lower prevalence of 3.6%. This low prevalence may be possibly due to the lower age group of the study sample compared to the present study.…”
Section: Discussionmentioning
confidence: 91%